DINAMIKA IDGHĀM PADA TASHRĪF FI'IL TSULĀTSĪ: ANALISIS SHOROF KLASIK DAN KONTEMPORER - Nurhayati (Yayasan Haiah Nusratul Islam, 2025)
This study examines the dynamics of idghām in the tashrīf (morphological derivation) of triliteral Arabic verbs (fi‘il tsulātsī) through classical and contemporary approaches. Idghām, a phonological assimilation process, is not only fundamental in tajwīd but also crucial in Arabic morphology. Classical perspectives, as seen in the works of scholars like Sibawaih and Ibn Jinni, focus on traditional phonetic rules, whereas contemporary analyses apply modern phonological frameworks such as Optimality Theory. This research identifies various types of idghām including mitslayn, mutajanisayn, and mutaqāribayn and explores their influence on meaning and morphological structure. Findings reveal that idghām contributes to semantic intensification, articulation efficiency, and morphosyntactic harmony. The study emphasizes the need to integrate classical insights with modern linguistic theory for a comprehensive understanding of Arabic. The results aim to enrich Arabic language instruction and advance Arabic linguistic studies both theoretically and practically.